1993
DOI: 10.3133/wri924106
|View full text |Cite
|
Sign up to set email alerts
|

Development, calibration, and testing of ground-water flow models for the Mississippi River Valley alluvial aquifer in eastern Arkansas using one-square-mile cells

Abstract: Development of digital groundwater flow models of the Mississippi River Valley alluvial aquifer in eastern Arkansas was prompted by the growing concern about large water-level declines in the alluvial aquifer and by the need to better understand the flow system. Several flow models have been developed previously, but at scales that are too large for analyzing the effect of future pumping at a farm or local scale. Models developed and described in this report are at a one-square-mile cell scale that can be used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Previous groundwater studies in the Mississippi Alluvial Plain area, primarily those using groundwater flow models to study the groundwater system, have suggested groundwater recharge rates for the alluvial plain that range from less than 1 inch per year to no greater than 5 inches per year (see, for example, Ackerman, 1989Ackerman, , 1996Sumner and Wasson, 1990;Mahon and Poynter, 1993;Stanton and Clark, 2003;Clark and others, 2013;Killian and others, 2019;Gratzer and others, 2020;Wacaster, 2020). Pumping in the alluvial aquifer has drawn down the water table extensively, resulting in an induced increase in recharge over predevelopment rates (Ackerman, 1989(Ackerman, , 1996.…”
Section: Previous Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous groundwater studies in the Mississippi Alluvial Plain area, primarily those using groundwater flow models to study the groundwater system, have suggested groundwater recharge rates for the alluvial plain that range from less than 1 inch per year to no greater than 5 inches per year (see, for example, Ackerman, 1989Ackerman, , 1996Sumner and Wasson, 1990;Mahon and Poynter, 1993;Stanton and Clark, 2003;Clark and others, 2013;Killian and others, 2019;Gratzer and others, 2020;Wacaster, 2020). Pumping in the alluvial aquifer has drawn down the water table extensively, resulting in an induced increase in recharge over predevelopment rates (Ackerman, 1989(Ackerman, , 1996.…”
Section: Previous Investigationsmentioning
confidence: 99%
“…Pumping from this aquifer and underlying aquifers supplies water for the irrigation of crops, aquaculture, drinking water for urban areas, industrial supply, and other uses (Clark and others, 2011;Lovelace and others, 2020). The heavy use of this aquifer has caused substantial groundwater level declines in the alluvial plain of Arkansas and Mississippi, which has motivated a large number of hydrologic studies by the USGS aimed at understanding groundwater movement in the system of aquifers in the area and the potential effect of increasing or reducing pumping on groundwater supply and availability (Boswell and others, 1968;Cushing and others, 1970;Broom and Reed, 1973;Brahana and Mesko, 1988;Ackerman, 1989Ackerman, , 1996Mahon and Ludwig, 1990;Sumner and Wasson, 1990;Arthur and Taylor, 1998;Arthur, 2001;Brahana and Broshears, 2001;Mahon and Poynter, 1993;McKee and Clark, 2003;Reed, 2003;Stanton and Clark, 2003;Kresse and Clark, 2008;Clark and Hart, 2009;others, 2011, 2013).…”
Section: Introductionmentioning
confidence: 99%